Optimizing Virus Identification in Critically Ill Children Suspected of Having an Acute Severe Viral Infection*. Issue 4 (April 2016) - Randolph, Adrienne G.; Agan, Anna A.; Flanagan, Ryan F.; Meece, Jennifer K.; Fitzgerald, Julie C.; Loftis, Laura L.; Truemper, Edward J.; Li, Simon; Ferdinands, Jill M.
Abstract : Objectives: Multiplex rapid viral tests and nasopharyngeal flocked swabs are increasingly used for viral testing in PICUs. This study aimed at evaluating how the sampling site and the type of diagnostic test influence test results in children with suspected severe viral infection. Design: Prospective cohort study. Setting: PICUs at 21 tertiary pediatric referral centers in the United States. Patients: During the 2010–2011 and 2011–2012 influenza seasons, we enrolled children (6 mo to 17 yr old) who were suspected to have severe viral infection. Interventions: We collected samples by using a standardized protocol for nasopharyngeal aspirate and nasopharyngeal flocked swabs in nonintubated patients and for endotracheal tube aspirate and nasopharyngeal flocked swabs in intubated patients. Measurements and Main Results: Viral testing included a single reverse transcription-polymerase chain reaction influenza test and the GenMark Respiratory Viral Panel (20 viruses). We enrolled 90 endotracheally intubated and 133 nonintubated children. We identified influenza in 45 patients with reverse transcription-polymerase chain reaction testing; the multiplex panel was falsely negative for influenza in two patients (4.4%). Six patients (13.3%) had not been diagnosed with influenza in the PICU. Non-influenza viruses were identified in 172 of 223 children (77.1%). In nonintubated children, the same virus was identified by nasopharyngeal flocked swabs and nasopharyngeal aspirate in 133 of 183 paired samples (72.7%), with +nasopharyngeal aspirate/–nasopharyngeal flocked swabs in 32 of 183 paired samples (17.4%). In intubated children, the same virus was identified by nasopharyngeal flocked swabs and endotracheal tube aspirate in 67 of 94 paired samples (71.3%), with +nasopharyngeal flocked swabs/– endotracheal tube aspirate in 22 of 94 paired samples (23.4%). Most discrepancies were either adenovirus or rhinovirus in both groups. Conclusions: Standardized specimen collection and sensitive diagnostic testing with a reverse transcription-polymerase chain reaction increased the identification of influenza in critically ill children. For most pathogenic viruses identified, results from nasopharyngeal flocked swabs agreed with those from nasopharyngeal or endotracheal aspirates. Abstract : Supplemental Digital Content is available in the text.